The Impact of Maladaptive Perfectionism and Parental Expectation on Self-Critical Rumination Among Young Adults - Irfa Irfan; Iqra Batool; Amina Bibi; Nayab Sajid; Ayesha Asghar (Indus Journal of Social Sciences, 2025)
Purpose: This present study aims to explore the impact of maladaptive perfection and parental expectations on self-critical rumination among young adults Pakistan. It is hypothesized that there will be a significant relationship between maladaptive perfectionism, parental expectation and self-critical rumination among young adults. Design: A sample N=200 participants was taken from young adults age of 18-30 of Lahore, Pakistan. This study was conducted on both male and female participants. According to the study around 50.5% female and 49.5% were male. The assessment tool employed in the study include Frost Multidimensional Perfectionism Scale (FMPS), the Parental Expectation Scale, and Self-Critical Rumination Scale (SCRS). Methodology/approach: Data analysis involve Pearson’s correlation revealed positive between maladaptive perfectionism, parental expectation and self-critical rumination. Multiple linear regression analysis shows that both maladaptive perfectionism and parental expectation significant predict self-critical rumination. Internal consistency of scales was checked by seeing the Cronbach’s alpha value of three scales. Findings: results showed that there is likely to be a significant positive relationship between maladaptive perfectionism, parental expectations and self-critical rumination. Further-more self-critical rumination positively predictor of maladaptive perfectionism and parental expectation among young adults.